ANALISIS PERLINDUNGAN KONSUMEN TERHADAP TANGGUNG JAWAB PELAKU USAHA MEMPRODUKSI OBAT SIRUP CAIR YANG MENIMBULKAN GAGAL GINJAL AKUT PADA ANAK - Ahmad Sopian Sauri,; Yuniar Rahmatiar,; Muhamad Abas, (The Juris, 2023)
The purpose of this research is to find out how business actors are responsible for consumer losses according to the Consumer Protection Act in Indonesia and to find out how legal protection is for consumers who are harmed by business actors both in civil and criminal law, with a case study of acute kidney failure in children caused by consuming syrup drug products. Business activities carried out by business actors in producing a product can be in the form of goods and/or services that can provide a sense of security, comfort, safety and do not pose a danger to consumer health. Products produced and traded by business actors must meet quality standards, provide correct, honest and clear information on products produced and traded after going through tests and inspections by BPOM. The method used in this research is the normative research method while the data analysis technique is obtained by using legal reasoning techniques. The results of this study can be concluded that business actors committed violations in producing children's syrup drugs using dangerous drug mixtures due to use that exceeds the threshold. Civil responsibility, providing compensation and compensation to the victim's family. Criminal liability, namely imprisonment for a maximum of 10 years and a fine of up to Rp. 1 billion. In addition to guaranteeing consumer rights in the UUPK, criminal sanctions are regulated as a preventive and repressive measure for violations committed by business actors against the rights of consumers aimed at protecting the rights of consumers who feel disadvantaged in buying and selling transactions between business actors.